Internal and External Cubic Subalgebras of BCK/BCI-Algebras - Bordbar, Hashem; Zahedi, Mohammad Mehdi; Jun, Young Bae (Journal of the Indonesian Mathematical Society, 2021)
A characterization of cubic subalgebra is established. The notion of internal and external cubic subalgebra in BCK/BCI-algebra and several properties are investigated. The R-union, R-intersection, P-union, and P-intersection of internal and external cubic subalgebras in BCK/BCI-algebra are discussed.